Geography of diseases in Peru in relation to climatic zones - Weiss H., Pedro (1954)
Those who were interested in classifying climates Peru unanimously lament the paucity of data. In many parts of the territory is no reference at all and only a few places there sufficiently rigorous and prolonged observations.